Identification Of Insect Diversity in Coffee Plants at Various Heights of Citaman Lawang Taji Gunung Karang Pandeglang Plantations - Isnaeni, Dwi; Laila, Alfu; Eiffelt Rossaffelt Rumbiak, Julio; Saylendra, Andree (Sam Ratulangi University, 2025)
Coffee (Coffea sp) is a significant plantation crop in Indonesia. Smallholder farmers grow it using environmentally friendly management systems that keep soil fertile and the biodiversity high. This research utilizes a quantitative descriptive methodology. We collected data by directly observing the field and using trapping methods. In three different places, they used pitfall traps, yellow pan traps, and light traps. Purposive sampling was used to choose the place where samples would be taken. There were four samples taken, each one a week apart. After identifying and analyzing the insect that had been collected, we used ANOVA with F tables of 1% and 5% to find their diversity, dominance, and evenness. The findings indicated that 6 orders and 21 families were recognized from the three sites. The diversity indices for locations I, II, and III were classified as medium (1.51), low (-0.11), and medium (1.99), respectively. The dominance indices for sites I, II, and III were classified as low (0.44), low (0.11), and low (0.21), respectively. The evenness index for locations I, II, and III was low (0.26), low (-0.02), and moderate (0.44), respectively. Keywords: Identification, Diversity, Insects, Coffee, Diversity, Pandeglang